Ikrah (Marital Coercion) and Divorce Before Dukhul in Turun Ranjang Marriage: A Socio-Legal Analysis of Jantho Sharia Court Decision No. 277/Pdt.G/2024/Ms.Jth - Yuspita Sari, Delvina; Djawas, Mursyid; Husnul, Muhammad (Universitas Islam Negeri Alauddin Makassar, 2026)
Previous studies on turun ranjang marriage such as those by Ihsan (2019), Siti Rif’ah (2022), and Ridhai Saifirai (2021 primarily focus on normative Islamic law and Acehnese customary perspectives, emphasizing its permissibility and social function. However, these works do not specifically examine how judicial institutions assess coercion (ikrah) in such marriages, nor do they analyze the legal consequences of divorce before dukhul through a concrete court decision. This study addresses that gap by providing a socio-legal analysis of coercion and pre-consummation divorce in turun ranjang marriage based on Jantho Sharia Court Decision No. 277/Pdt.G/2024/MS.Jth. This research employs qualitative field research using a case and statutory approach. Data were collected through document analysis of the court decision and in-depth interviews conducted between February and August 2025 with four key informants: one panel judge of the Jantho Sharia Court, one Head of KUA Indrapuri, one village imam, and one village secretary of Gampong Lampanah Tunong. The data were analyzed using an Islamic legal framework that operationalizes the concepts of ikrah (coercion), ridha (free consent), ‘urf sahih (legitimate custom), and the objectives of marriage (sakinah, mawaddah, rahmah) as analytical parameters for assessing marital validity. The findings demonstrate that although turun ranjang marriage is formally valid under Islamic and Indonesian law, the presence of psychological coercion fundamentally undermines its ethical legitimacy. The couple never cohabited nor consummated the marriage, and persistent conflict arose from the outset. The court granted divorce on the basis of continuous disputes and proven emotional pressure, and ordered the return of half of the dowry in accordance with Qur’an Surah Al-Baqarah (2:237) and Article 35(1) of Law No. 1 of 1974 due to the divorce occurring before dukhul. This study contributes a novel perspective by integrating doctrinal Islamic principles with empirical judicial analysis, demonstrating that marital validity is not determined solely by compliance with formal pillars (rukun), but by the substantive presence of ridha and the absence of ikrah.